Entrepreneurship success traits. Do Kenyans possess the desired entrepreneur personality traits for enhanced E-entrepreneurship? Case study of Kenyan students in the people's republic of China - Stephen Mungone Shimoli; Wenzhao Cai; Muhammad Hasnain Abbas Naqvi; Qiaoqi Lang (Cogent Business & Management, 2020)
An individual's behavior can be determined by the personality traits they possess, which are a description of a set of characteristics that are unique to the individual. Previous analyses have indicated that the Big-5 personality traits (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) predict the likelihood of intention, creation, and success in business ventures (Brandstätter, 2011), while narrow personality traits such as Extraversion and Conscientiousness have also been found to predict the entrepreneurial success more precisely (Rauch & Frese, 2007). This study aimed at finding out if 518 Kenyans possessed the right personality traits that would determine their E-entrepreneurship success or failure in online business ventures. The study also sorts to make a difference by merging the Big-5 personal traits with self-efficacy, Need for achievement, and Locus of control. To analyze the relationship between personality traits, entrepreneur success, and online business ventures in the Kenyan context, data was analyzed quantitatively through descriptive and inferential analysis with the sample population from Kenyan international students in The People's Republic of China. The results indicate that majority of the students have a high score in openness to experience, Conscientiousness, Neuroticism, Locus of control, and Self-efficacy.
Keywords: 650; E-entrepreneurship; personality traits; entrepreneur success; big-5; self- efficacy; locus of control; need for achievement